Effect of Adding Kaffir Lime Leaf Powder (Citrus hystrix) and Citronella Leaf Powder (Cymbopogon nardus) in Salted Egg on pH, Antioxidant, Moisture Content, and Organoleptics - Ardiyanti Rahma Setiawati; Dedes Amertaningtyas; Ahmad Khoirul Umam (Jurnal Ilmu dan Teknologi Hasil Ternak)
Salted egg is a well-known traditional product, particularly in many Asian countries, where it is valued for its unique savory taste, extended shelf life, and convenience. Consumer demand for healthier, more appealing food has sparked interest in enriching salted eggs with natural ingredients. The purpose of this study was to analyze the effect of adding kaffir lime leaf powder (Citrus hystrix) and citronella leaf powder (Cymbopogon nardus) to salted eggs on pH, antioxidants, moisture and organoleptics. The research method used was experimental using a completely randomized design (CRD) with 6 treatments and 3 replications. The treatment of lime leaf powder and lemongrass leaf powder addition rates are 0%, 2.5%, 5%, 7.5%, 10% and 12.5%. The data was analyzed using Analysis of Variance (ANOVA), if there is a real influence it will be tested using the Duncan test. The results of the study showed a very significant difference (p < 0.01) on antioxidants and organoleptics, and significant difference (p < 0.05) on pH value. Meanwhile, the addition of kaffir lime leaf powder and citronella leaf powder to salted eggs showed no significant difference (p > 0.05) on moisture content. Average pH value 7.05-7.84; antioxidant 1.46- 10.85 %; moisture content 55.13- 67.87%; organoleptic aroma 3.44-4.02; taste 3.58-4.08. This score range reflects how the participants perceived the aroma and rated the taste of the salted eggs. The conclusion of this research is the best treatment with the addition of kaffir lime leaf powder  and citronella leaf powder as much as 12.5%.